Indian mithology as buddhism catecism. Vedic terminology and references to Indian cosmology in the Konjakumonogatarishū - Villamor Herrero, Efraín (Estudios Complutenses de Asia Oriental, 2025)
Indian Buddhist narratives were translated from classic Chinese in the Japanese collection known as Konjakumonogatarishū (KON). Numerous tales and mythological figures of ancient India constituted a part of Japanese folklore due to this type of literary adaptation. Its Indian section is formed not only by many of the most idiosyncratic tales that compound the hagiography of Gautama Buddha but also portrayed how the heterogeneous religious background of ancient India was transmitted in medieval Japan. This work analyses the Vedic terminology and references to the Indian cosmology in the KON, focusing on its Indian section. The achievements of this study show the interpretation and catechism implied in these references, which expose the authentic intention of its editors.